Strategi dan Pendekatan Pembelajaran Bahasa Arab yang Efektif untuk Meningkatkan Kompetensi Siswa - Nailatuz Zamrudiah; Muhammad Akhyat Syahbani; M. Yunus Abu Bakar (Educational Journal, 2026)
Arabic language learning plays a crucial role in Islamic education and in developing students' communicative competence. However, in practice, various problems remain, particularly the use of teacher-centered learning approaches that lack active student involvement. This study aims to analyze effective Arabic language learning strategies and approaches to improving student competence. The method used was a literature review, examining various relevant scientific sources, such as journals, books, and research articles. The results of the study indicate that an effective learning approach is student-centered, combined with Multiple Intelligences theory and a communicative approach. This approach can improve students' activeness, motivation, and overall language skills, including listening, speaking, reading, and writing. Furthermore, active and collaborative learning strategies, along with the use of authentic media and evaluation, also contribute significantly to improving the quality of learning. Thus, the integration of various innovative approaches and strategies can create more effective, interactive, and student-centered Arabic language learning that meets the needs of modern learners.